Concurrent primaries of vaginal clear cell adenocarcinoma and endometrial adenocarcinoma in a 39-year old woman with in utero diethylstilbestrol exposure. Issue 3 (1st May 2001) - Keller, C.; Nanda, R.; Shannon, R. L.; Amit, A.; Kaplan, A. L.
Abstract : Diethylstilbestrol (DES) was used widely in the late 1940s in an attempt to prevent adverse pregnancy outcomes. In 1971 the US Food and Drug Administration proscribed its use for pregnancy support secondary to its association with clear cell adenocarcinoma of the vagina. Several studies in animal models demonstrated an association with endometrial cancer among offspring following in utero DES exposure. To date, there is only one case report of endometrial cancer in women exposed to DES in utero . We present the first case, to our knowledge, of a woman exposed to DES in utero who presented with double primaries of clear cell cancer of the vagina concomitant with endometrial cancer.